Collaborative Teacher Inquiry into iPad Use in Grade 3 Classrooms: Mobilizing Knowledge through a Long-Term School-University Partnership - McQuirter Scott, Ruth; Dortmans, Donna; Rath, Cathy; Meeussen, Nancy; Boin, Jennifer (Brock education, 2015)
In this paper, we report on a longitudinal case study exploring Grade 3 teachers' implementation of iPads in the Language Arts classroom. A school-university partnership was formed based on a collaborative teacher inquiry model. We examined factors that shaped our collaboration. The project resulted in greater teacher sharing of iPad implementation strategies and growth in leadership skills among the teachers. A surprising finding was the degree of reciprocal learning about digital pedagogy that the university researchers experienced during the study and were able to share with their Pre-service Education classes. We emphasize the potential of school-university partnerships for narrowing the current gap between theory and practice in technology-enhanced learning.